Female mating failure and the failure of 'mating' in sterile insect programs. Issue 1 (13th August 2012) - Pérez‐Staples, Diana; Shelly, Todd E.; Yuval, Boaz
Abstract The sterile insect technique (SIT) involves the inundative release of irradiated (sterile or partially sterile) insects to decrease population levels in a target pest species. The effectiveness of SIT programs depends on sterile males mating successfully and inducing reproductive failure in wild females, or in the F1 generation in the case of lepidopteran species. Thus, from the perspective of insect control, female mating failure involves mating with a mass‐reared, sterilized male, which then results in female reproductive failure. Here, we review female mating failure in the context of SIT at two stages. First, at the pre‐copulatory stage we consider factors that affect female mating failure with sterile males, such as differences between sterile and wild males in terms of male courtship success, male discrimination of females, pheromone production, and dispersal. We emphasize studies with some degree of ecological realism and review certain factors that can affect female sexual development and choice, such as diet, age, and sex ratio. Second, at the post‐copulatory stage we consider factors that functionally result in female reproductive failure, such as ejaculate transfer and control of female remating. Sterile insect technique operations strive to incorporate methods that increase wild female mating with sterile males so that ultimately population‐wide reproductive failure is achieved in the target species.